Time And Cost Controlling Using Critical Path Method (Case Study At Palur Fly-Over Surakarta) - Elsosan, Adel Issa, Mohammad Solikin, Ph.D, Ir. M. Nur Sahid, M.T., M.M (2015)
ABSTRACT-The purpose of this study is to (1.To analyze the remaining work items at month of 14th from the project starts, 2). To analyze the remaining cost items at month of 14th after the project start. And the last is 3). To reschedule and to optimize the time and cost by use Critical Path Method (CPM). This study will analyze time and cost controlling by using CPM approach on the project. Based on the background of the study, the statements of the problems can be formulated as follows: (1) How is rescheduling in optimization of time on Palur Fly over of Surakarta by using Critical Path Method (CPM)? and (2) How is the implement of the normal and the crash of the cost on Palur flyover in Surakarta by using Critical Path Method (CPM)?. The writer analyzed the fly-over project implementation fly over Palur in Surakarta whether according to the time plan. By rescheduling the plan and make optimization of time and minimizing cost with CPM (Critical Path Method). Based on the result and discussion, the conclusion of this research as follows: The implementation of the project is not in accordance with the plan, it is too late because of the weather and can be solved by increasing the valve of workers. Based on the rescheduling alternatives can be implemented as the alternative I with 160 days shorter and the rest of cost Rp 32.556.381.150